The Influence of Local Wisdom Bapukung on Productivity and Role Balance of Housewives - Cahya, Nila; Prabowo, Sigit Dwi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Balancing caregiving duties with multiple responbilities is a persistent challenge for housewives, particularly those managing micro, small, and medium enterprises (MSMEs). Bapukung, a traditional swaddling practice from South Kalimantan, offers a potential solution by improving infant sleep quality and providing mothers with uninterrupted time to manage household and business tasks. This study investigates the influence of Bapukung on the productivity and role balance of housewives using a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS). Data were collected from 30 respondents in South Kalimantan through structured questionnaires. Results reveal that Bapukung significantly influences both productivity (β = 0.816, p < 0.05) and role balance (β = 0.787, p < 0.05). These findings align with the Resource-Based View (RBV) and Balanced Scorecard frameworks, demonstrating how cultural practices can serve as strategic resources to enhance time management and efficiency. The study contributes to the integration of local wisdom into modern management theories, offering practical implications for family welfare programs and entrepreneurship training. Future research should explore the scalability of Bapukung across diverse cultural contexts and its long-term influence on family dynamics and maternal well-being.